IS WHOM YOU ASK IMPORTANT? REPORTING OF MEDICATION USE BY SELF- AND PROXY-RESPONDENTS. (11th November 2018) - Oksuzyan, A; Sauer, T; Gampe, J; Hoehn, A; Wod, M; Christensen, K; Wastesson, J
Abstract: Background: The present study investigates the accuracy of the reporting of medication use by proxy- and self-respondents, and it compares the prognostic value of the number of medications from survey and registry data for predicting mortality across self- and proxy-respondents. Methods: The study is based on the linkage of the Longitudinal Study of Aging Danish Twins and the Danish 1905–Cohort Study with the Danish National Prescription Registry. We investigated the concordance between survey and registry data, and the prognostic value of medication use when assessed using survey and registry data, to predict mortality for self- and proxy-respondents at intake surveys. Results: Among self-respondents, the agreement was moderate (kappa from 0.52 to 0.58) for most therapeutic groups; while among proxy-respondents, the agreement was low to moderate (kappa from 0.36 to 0.60), and was lower than among self-respondents. The magnitude of the relative differences was, generally, greater among proxies than among self-respondents. Each additional increase in the total number of medications was associated with 7–8% mortality increase among self- respondents and 4–6% mortality increase among proxy-respondents in both the survey and registry data. The predictive value of the total number of medications estimated from either data source was lower among proxies (c-statistic = 0.56–0.58) than among self-respondents (c- statistic = 0.74). Conclusions: The concordance between survey and registry data regarding medication use and the predictive value of the number of medications for mortality were lower among proxy- than among self-respondents.